The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pmed.1004235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antibiotics on gut microbiome composition and resistome in the first years of life in low- to middle-income countries: A systematic review

Abstract: Background Inappropriate antimicrobial usage is a key driver of antimicrobial resistance (AMR). Low- and middle-income countries (LMICs) are disproportionately burdened by AMR and young children are especially vulnerable to infections with AMR-bearing pathogens. The impact of antibiotics on the microbiome, selection, persistence, and horizontal spread of AMR genes is insufficiently characterized and understood in children in LMICs. This systematic review aims to collate and evaluate the available literature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
(212 reference statements)
0
6
0
Order By: Relevance
“…Considering the dynamic nature of the gut microbiome and the fact that host genetics alone do not exclusively determine its diversity, we additionally adjusted for external gut microbiota-associated factors including healthy dietary components (intake of fiber, vegetables, fruit, whole grains, and poultry; g day −1 ), [35][36][37] geographic location (England area or non-England area), 38 and antibiotic usage as a child or a teenager (yes, no). 39 Stratification and interaction analyses were also conducted for the PGS of the eGFR to evaluate the modification effect of the genetically predicted eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the dynamic nature of the gut microbiome and the fact that host genetics alone do not exclusively determine its diversity, we additionally adjusted for external gut microbiota-associated factors including healthy dietary components (intake of fiber, vegetables, fruit, whole grains, and poultry; g day −1 ), [35][36][37] geographic location (England area or non-England area), 38 and antibiotic usage as a child or a teenager (yes, no). 39 Stratification and interaction analyses were also conducted for the PGS of the eGFR to evaluate the modification effect of the genetically predicted eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, antibiotics can have broad impacts on the microbiome, targeting not only the causative agent but also commensal organisms. Antibiotics disrupt the healthy balance of gut flora, leading to a reduction in diversity and changes in both populations and functions [72,73]. This disruption can also contribute to the spread of antibiotic resistance.…”
Section: Mechanisms Of Microbiome-mediated Pathogenesismentioning
confidence: 99%
“…The number of studies reporting the presence and source of antibiotic resistance genes (ARGs) in infants has increased drastically owing to the dire situation created by the increasing spread, abundance, ubiquitous nature of ARGs and the high abundance of ARGs reported in Low – to Middle – income countries. 16 , 17 Recent studies have shed light on ARG abundance and the extent to which several factors affect it. 16 , 18–20 Studies have demonstrated a high abundance of ARGs in infants, even in the absence of antibiotic exposure, making the infant gut a reservoir of ARGs.…”
Section: Introductionmentioning
confidence: 99%